SELF MANAGEMENT BERHUBUNGAN DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA - Edriyani Yonlafado Br. Simanjuntak; Tri Krisman Lombu (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2018)
The health problem in the world as a massive killer of which was chronic kidney failure, progressive and difficult to cure, caused an imbalance of metabolism, fluid and electrolytes. In dealing with patients with chronic kidney failure, one of the ways was to increase the ability in self-mangement to be effective in order to improve the quality of life of patients. This study aims was determine the relationship of self management with quality of life in patients with chronic renal failure in the hemodialysis unit. This research is a quantitative research with correlation analytic design using a cross sectional approach. The population is all patients with chronic kidney failure who undergoing hemodialysis in the hemodialysis unit with a sampling technique using purposive sampling method with a total sample of 164 people. The method of collecting data using a questionnaire using the spearman test. The results was show that the majority of self management was not good (53.9%), the quality of life of the majority (not good) was 51.5% and the relationship of self management with quality of life showed p value 0,000 <Î± 0,05 r = 0,880 indicating that there were self management relationships with quality of life with close relations are very strong. The conclusion was that the lower the self management, the lower the quality of life of patients with chronic renal failure undergoing hemodialysis. It was recommended that health workers in the hemodialysis unit always teach the importance of self management and motivate patients to continue to improve their quality of life.